The changing of the French labor market, 2000-2017 - Philippe Askenazy (IZA World of Labor, 2018)
France has the second largest population in the EU. Since 2000, the French labor market has undergone substantial changes resulting from striking trends, some of which were catalyzed by the Great Recession. The most interesting of these have been the massive improvement in the education of the labor force (especially of women), the resilience of employment during the Great Recession (albeit with a very late recovery), and the dramatic emergence of very short-term employment contracts and low-income independent contractors, which together fueled earnings inequality.
Keywords: J01; J08; O52; 330; education; unemployment; short-term jobs; independent contractors; inequality; France